2008
DOI: 10.1016/j.joca.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced signaling pathways in hyalin chondrocytes: inhibition by Avocado–Soybean Unsaponifiables (ASU)

Abstract: These results demonstrate that ASU express a unique range of activities, which could counteract deleterious processes involved in OA, such as inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
(30 reference statements)
2
50
0
2
Order By: Relevance
“…Results from this study suggest that the ASU + EGCG combination may exert a COX-independent effect mediated, at least in part, through NF-κB inhibition. Gabay et al (2008) showed ASU alone to decrease MMP-3 and -13 expression, PGE 2 synthesis, as well as prevent NF-κB nuclear translocation and inhibit the ERK1/2 signaling pathway in stressed hyalin chondrocytes [28]. Another study has shown EGCG to inhibit LPS-induced IκBα degradation, NF-κB nuclear translocation, and NF-κB DNA binding activity in bone marrow-derived macrophages (BMMs) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Results from this study suggest that the ASU + EGCG combination may exert a COX-independent effect mediated, at least in part, through NF-κB inhibition. Gabay et al (2008) showed ASU alone to decrease MMP-3 and -13 expression, PGE 2 synthesis, as well as prevent NF-κB nuclear translocation and inhibit the ERK1/2 signaling pathway in stressed hyalin chondrocytes [28]. Another study has shown EGCG to inhibit LPS-induced IκBα degradation, NF-κB nuclear translocation, and NF-κB DNA binding activity in bone marrow-derived macrophages (BMMs) [25].…”
Section: Resultsmentioning
confidence: 99%
“…The MEK1/2 inhibitor PD198306, which blocks ERK activation, also reduced the severity of OA lesions in a rabbit model of OA (30). Furthermore, avocado-soybean unsaponifiables (ASU), which are used to treat OA in Europe, were reported to inhibit IL-1β-induced ERK activation, but not p38 kinase or JNK activation, in chondrocytes in vitro (31). These results suggest that inhibition of ERK activation is sufficient to reduce OA lesions.…”
Section: +mentioning
confidence: 86%
“…Isolation of costal cartilage from KO, or WT 7-day-old mice, and chondrocytes plating were adapted from Gabay et al [17]. Briefly, pieces of costal cartilage were incubated in collagenase 3 mg/mL for 1 h 30 min at 37 °C, carefully isolated from soft tissue in PBS, incubated in collagenase 0.5 mg/mL overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Passages 0 and 1 chondrocytes were used for experiments because cartilage marker genes maintained expression. Monolayer cultures were maintained in culture conditions, as previously described [17], and growth medium was replaced every 3 days. Prior to analysis, cells were rinsed with PBS, trypsinized with Trypsin 0.25%, resuspended in 10 ml of growth medium, and counted with a hemocytometer using trypan blue exclusion assay.…”
Section: Methodsmentioning
confidence: 99%